Literary Traces of the Qur`an in Its English Translations (Language Circle: Journal of Language and Literature, 2018)
Based on many researches have been done, the Qur‘an uses literary methods in conveying the messages. This research uses different perspective in proving such conclusion by using English translations of the Qur‘an written by four authorized Qur‘an translators. The researcher uses Hermeneutics and Aesthetics to find the literary substantiations of English translations of the Qur‘an. Of course there will be random verses of the Qur‘an that would be choosen to be analyzed. Both analysis devices say that English translations of the Qur‘an have literary traces that signify the Qur‘an as a literary masterpiece, such as not only in owning different dictions and layers of meaning but also in owning aesthetic process and poetic texts.